KARAKTERISTIKEKSTRAK AIR DAUN PUGUNTANO [Curanga fel-terrae (Lour.) Merr.] YANG BERPOTENSI SEBAGAI ANTELMINTIK - Popi Patilaya; Dadang Irfan Husori (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
OBJECTIVE: This study aimed to determine the characteristics of the water extract of leaves puguntano (Curanga fel-terrae (Lour.) Merr.) Using spectroscopic methods and phytochemical screening.METHODOLOGY: phytochemical screening performed to analyze compounds alkaloids, flavonoids, glycosides, anthraquinone glycosides, saponins, tannins, cyanogenic glycosides, and triterpenoids / steroids. Analyses were performed using FTIR spectrophotometer (Shimadzu) with IR Solution software. The wavelength is set at 4000 – 400 cm-1 with a resolution of 4 cm-1 and 16 scanner.RESULTS: Puguntano leaf water extract contains flavonoids, glycosides, saponins, tannins, steroids, and terpenoids. Infrared spectrum of puguntano leaf aqueous extract showed a O – H fuctional group at 3313.71 cm-1, C – H at 2974.23 and 2881.65 cm-1, C = C at 1689.65 and 1597.06 cm-1, C – O at 1265.30 and 1076.28 cm-1 and group C – H aromatics at 813.96 cm-1 in the fingerprint region